2010
DOI: 10.1016/j.jfms.2009.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fluticasone propionate dosage in an experimental model of feline asthma

Abstract: Cats with inflammatory bronchial disease are usually treated with glucocorticoid (GC) drugs to reduce airway inflammation. Inhalant GC delivery can preserve airway effects while systemic effects are minimized. An appropriate dosage regimen for inhaled GC in cats has not been investigated. A blinded, randomized, cross-over study design was used to investigate the ability of three different dosages of the inhalant GC fluticasone propionate delivered by metered dose inhaler to ameliorate eosinophilic airway infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
15

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 38 publications
0
31
0
15
Order By: Relevance
“…Only one study assessed three different doses in a model of feline asthma and demonstrated that airway inflammation was similarly improved regardless the dose of inhaled fluticasone (Cohn et al . ). Based on this observation and regarding the pharmacokinetic considerations in dogs and humans discussed above, getting a better clinical response by increasing dosage in dogs with EBP appears unlikely.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Only one study assessed three different doses in a model of feline asthma and demonstrated that airway inflammation was similarly improved regardless the dose of inhaled fluticasone (Cohn et al . ). Based on this observation and regarding the pharmacokinetic considerations in dogs and humans discussed above, getting a better clinical response by increasing dosage in dogs with EBP appears unlikely.…”
Section: Discussionmentioning
confidence: 97%
“…2014. In cats, IST is also used for the management of experimental asthma (Cohn et al . 2010 ) and spontaneous chronic bronchial disease (Allerton et al .…”
Section: Introductionmentioning
confidence: 99%
“…, Cohn et al . ). The uncontrolled character of this study represents a major limitation, as cases were selected retrospectively and iB therapy was the standard treatment regimen for all cats included during the observation period.…”
Section: Discussionmentioning
confidence: 97%
“…A recent study in cats with experimentally induced asthma evaluating different dosages of iGC showed that airway eosinophilia was reduced in all groups and did not differ significantly when cats received 44, 110 or 220 µg fluticasone twice daily for 3 weeks (Cohn et al . ). Therefore a lower dose of budesonide might also allow for disease control in cats with spontaneous asthma while minimising the effects on the HPAA axis.…”
Section: Discussionmentioning
confidence: 97%
“…, Cohn et al . ). Although aerosol therapy is widely advocated for the treatment of feline asthma (Padrid, , , Ettinger ) studies demonstrating a benefit in clinical cases are lacking.…”
Section: Introductionmentioning
confidence: 97%